2017
DOI: 10.4274/tod.85856
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Bone Mineral Density Measurements in Two Different Regions of Turkey

Abstract: Türkiye'nin İki Farklı Bölgesindeki Kemik Mineral Yoğunluğu Ölçümlerinin Karşılaştırılması Objective: It was aimed to compare the values of bone mineral density (BMD) measurements made of patients in the osteoporosis (OP) unit in the provinces of Muğla and Erzurum provinces and to determine OP prevelance. Materials and Methods: The data were evaluated of a total of 3862 patients aged over 50 years, who were included in the study. Of patients; ages, sex, and body mass index (BMI) were recorded. Patients in Muğl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…There was a statistically significant difference between the two cities in the age group of 40-49 and 50-59 years, and Kastamonu mean BMD was higher. Some of our results were compatible with the results of the study by Aslan et al [4] while some other results of ours seemed consistent with the results of İmerci et al [12]. Therefore, regional outcomes and differences are important factors in interpreting BMD values.…”
Section: Gulcu a Ve Ozkan O/ The Bone Mineral Density Values Of Women In Alanyasupporting
confidence: 93%
See 1 more Smart Citation
“…There was a statistically significant difference between the two cities in the age group of 40-49 and 50-59 years, and Kastamonu mean BMD was higher. Some of our results were compatible with the results of the study by Aslan et al [4] while some other results of ours seemed consistent with the results of İmerci et al [12]. Therefore, regional outcomes and differences are important factors in interpreting BMD values.…”
Section: Gulcu a Ve Ozkan O/ The Bone Mineral Density Values Of Women In Alanyasupporting
confidence: 93%
“…The authors noted that less of the sunlight exposure may be an effective factor in this. In contrast, İmerci et al [12] found that femur neck BMD values in the Muğla region were significantly lower than Erzurum region.…”
Section: Resultsmentioning
confidence: 87%